MODEL PENGATURAN PINTU AIR PLTA BERBASIS ARDUINO - Rosmania, Poppy (2013)
With the rapid advancement of technology today, the need for automation in the control floodgate. Final project is titled "Hydropower Floodgate Control Models Arduino Based" The project goal is to make the final water level control system and the opening and closing of floodgate through the computer. The final project is utilizing aluminum as sensor combined with the input circuit. Input circuits with transistors as switches and input of the circuit is routed to the Arduino. Arduino generate a voltage of 5 V. Voltage of 5 V will turn optocoupler transistor circuit then referred to as a switch to activate a relay to run the motor DC 12 V. The system is integrated with visual basic software as a form of visualization. From the results of measurements and experiments that have been carried out on the opening and closing of each door, the opening and closing of the door running well. Central lock driver circuit, water level input circuit works with the principle of a transistor as a switch. Will be active when the transistor base voltage of at least 0.7 V. Sensors are used on aluminum conductor is a material and use the media as an intermediary between the water source to the positive input circuit. Arduino as a tool that serves as a processing input data and produce output. Serial port component used for communication between visual basic and Arduino. In the central lock harness driver circuit transistor as a switch. To rotate the motor rotation direction by swapping the 12 V DC voltage source pole. Keywords: microcontroller, Arduino, Visual Basic, hydropower, Central lock